DIGITAL MEDIA-BASED LEARNING MEDIA FOR ELEMENTARY SCHOOL CITIZENSHIP EDUCATION - Arie Rahman; Devi Afriyuni Yonanda; Rida Fironika Kusumadewi (Universitas Majalengka, 2024)
Civic Education in elementary schools plays a crucial role in shaping students' character and understanding of national values. However, the application of digital media in Civic Education learning remains limited compared to other subjects. This research aims to examine the effectiveness of digital-based learning tools, specifically Augmented Reality, in enhancing students' understanding and engagement, while also providing recommendations for curriculum development and teacher training. The study employs a quantitative approach with an experimental design, comparing the learning outcomes of students using Augmented Reality media to those using conventional media. Data were collected through tests, questionnaires, and observations, and analyzed using descriptive and inferential statistics. The findings reveal that Augmented Reality significantly boosts students' motivation and comprehension, making learning more interactive and engaging, and aiding in the understanding of complex concepts through visualization. The research concludes that integrating digital media, particularly Augmented Reality, into Civic Education holds substantial potential to elevate educational quality in elementary schools. However, successful implementation hinges on teacher preparedness and adequate technological infrastructure, underscoring the importance of training and technical support for sustaining this innovation.